1988
DOI: 10.1111/j.1600-0447.1988.tb05080.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptomatology and drug compliance in schizophrenic patients

Abstract: The differences in the psychopathologic status of 26 complaint and 32 noncomplaint schizophrenic patients were evaluated on the basis of rating scales used at discharge. Noncomplaint patients had significantly higher scores for grandiosity, lack of feeling of illness and insight into it. Their score for global psychopathological state and disturbance in social adjustment was also significantly higher. The compliant patients had significantly higher score for self-rated depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
3
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(89 citation statements)
references
References 9 publications
5
79
3
2
Order By: Relevance
“…This finding contrasts with those of a number of authors who reported that schizophrenia patients have more difficulties implementing coherent actions because of disturbances in their formal thought processes [41]; that they are too locked into their productive-psychotic experience to take medication regularly [42]; that they have a partial feeling of well-being despite being in a state of psychosis [43]; and that they are incapable of understanding that they are ill [43]. The discrepancy between these reports and our findings may be explained by the fact that we used a sample of individuals with schizophrenia who received assessments during a stabilization phase.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding contrasts with those of a number of authors who reported that schizophrenia patients have more difficulties implementing coherent actions because of disturbances in their formal thought processes [41]; that they are too locked into their productive-psychotic experience to take medication regularly [42]; that they have a partial feeling of well-being despite being in a state of psychosis [43]; and that they are incapable of understanding that they are ill [43]. The discrepancy between these reports and our findings may be explained by the fact that we used a sample of individuals with schizophrenia who received assessments during a stabilization phase.…”
Section: Discussioncontrasting
confidence: 56%
“…On cross-sectional analyses, lack of insight has been closely linked to poor global functioning [24][25][26], and poor treatment compliance [27,28]. Lack of insight has also been closely associated with severe psychopathology [4,15,29], although inverse or no direct relationships have also been reported [8,16,30] Similarly, a number of studies have reported an inverse [31][32][33] but also positive [34][35][36] relationship between insight and positive symptoms, suggesting therefore that insight may be largely independent of psychopathology severity [37,38] as such, recent research interest has now been shifted onto specific symptom dimensions. For instance, weak to modest relationships have been reported between insight and anxiety [23,39,40] or depressive symptomatology [32,41,42].…”
Section: Introductionmentioning
confidence: 97%
“…In their review of the literature on postpsychotic depression, McGlashan and Carpenter (1976) conclude that these types of mood disorders arise from a lessening of defensive denial, which results in the patients becoming aware of the tragic circumstances of their illness. The finding that poor insight is positively correlated with elated mood and grandiosity has also been interpreted as evidence that poor insight serves a defensive function (Bartko et al, 1988, Heinrichs et al, 1985.…”
Section: Introductionmentioning
confidence: 99%